Annual planning meetings: views and perceptions. (December 2014) - Bindal, Taruna; Wall, David; Goodyear, Helen
Summary Background In 2009, annual face to face planning meetings (APMs) were introduced as an optional meeting for all paediatric trainees. APMs are a formative assessment process whereby the trainee meets with a panel of consultants and sets the agenda for discussion. Method A questionnaire about APMs was given to all participating trainees and trainers in 2011. Results The response rate was 93 per cent (139/150) and 67 per cent (12/18) for trainees and trainers, respectively. All trainers had received panel member training. Ninety‐one per cent of trainees (126/139) felt adequately prepared for the meeting. Issues discussed included career plans (93%), future training placements (73%), ePortfolio (61%) and previous training posts (61%). Trainees felt that the APM was a helpful formative assessment process (with a mean score of five on a six–point Likert scale: 1, strongly disagree; 6, strongly agree), and that panels were fair, supportive, communicated clearly, listened to concerns and focused on individual learning needs. Sixty‐seven per cent (8/12) of trainers would have liked more information about the process beforehand. Discussion The main benefits of APMs were trainees feeling supported in their training and better informed regarding career options. APMs would be of value to all specialties to enable annual formative assessment to be undertaken at a different time to the summative assessment process. APMs facilitate reflection on learning needs, and the formulation of personal development plans and career goals for trainees. <boxed-text content-type="pullQuote" position="anchor" orientation="portrait"> Trainees felt that the APM was a helpful formative assessment process </boxed-text>